Japan : the Hungry Guest. - Allen, G. C. (Taylor & Francis, 2010)
Written after the outbreak of war between Japan and China but putting aside British sentiments of suspicion, dislike and a sense of competition, G C Allen bases his observations of Japanese social, political and economic life on his first-hand experience of living and working in the country for a number of years. He argues that the economic expansion of Japan was regarded as a greater threat to Britain because of Japan's political aims and aggressive territorial expansion, but he is at pains to explain the Japanese domestic circumstances which gave rise to this situation.